PENGARUH FIRM SIZE, SOLVABILITAS, DAN FINANCIAL DISTRESS TERHADAP AUDIT DELAY - Fairuzzaman Fairuzzaman; Dwina Meila Azizah; Yuni Anggraeni (Unversitas Prof. Dr. Moestopo (Beragama), 2022)
The purpose of this study was to determine the effect of firm size, solvency, and financial distress on audit delay. This research includes quantitative research using secondary data obtained from the Indonesia Stock Exchange with the qualifications of the property and real estate sector companies for the 2017-2020 period. The sampling technique in this study used a purposive sampling method with a sample of 15 companies, with a total of 15 companies processed for 4 years, namely 60 data. Data analysis used multiple linear regression which was processed through SPSS. From the results of the analysis, it shows that firm size has a significant negative effect on audit delay, while solvency and financial distress have no significant positive effect on audit delay.